Leviticus 19:33-34 – the forgotten injunction: a case study of ‘alien’ students in Senga and Nehosho suburbs of Gweru, Zimbabwe - Mwandayi, Canisius (University Bamberg Press, 2016)
The Priestly material in Leviticus has for a long time been a devalued part of the Hebrew Bible. The general trend of modern scholarship tends to be characterized by a deep-seated bias that views impurity rules as primitive and irrational taboos, and sacrifice as controlled savagery that is empty of any spiritual meaning.